Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/jcph.1970
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Change in Serum Uric Acid After Administration of the Sodium‐Glucose Cotransporter 2 Inhibitor Luseogliflozin in Patients With Type 2 Diabetes Mellitus

Abstract: Although sodium-glucose cotransporter 2 (SGLT2) inhibitors lower serum uric acid, their long-term effect on uric acid metabolism is not well understood. We analyzed pooled data from studies wherein patients with type 2 diabetes mellitus received luseogliflozin, an SGLT2 inhibitor. Upon stratifying patients by baseline glycated hemoglobin (HbA 1c ) or serum uric acid, lower HbA 1c or higher serum uric acid level was associated with a greater reduction in serum uric acid after treatment. At week 12 of treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…Other control factors in the balance of serum UA can be volume status (enhances reabsorption) [ 46 , 47 ], low-salt diet (enhances reabsorption) [ 48 , 49 ], insulin [ 50 , 51 , 52 ], angiotensin II [ 53 ], epinephrine, and PTH, which raises serum UA through unknown mechanisms [ 54 ]. In addition, an important factor in controlling serum UA is oxidative stress, which modulates production, excretion, and reabsorption of urate [ 55 ].…”
Section: Uric Acid Excretionmentioning
confidence: 99%
“…Other control factors in the balance of serum UA can be volume status (enhances reabsorption) [ 46 , 47 ], low-salt diet (enhances reabsorption) [ 48 , 49 ], insulin [ 50 , 51 , 52 ], angiotensin II [ 53 ], epinephrine, and PTH, which raises serum UA through unknown mechanisms [ 54 ]. In addition, an important factor in controlling serum UA is oxidative stress, which modulates production, excretion, and reabsorption of urate [ 55 ].…”
Section: Uric Acid Excretionmentioning
confidence: 99%
“…However, it was also suggested that SGLT2i can cause hyperuricosuria ( Chino et al, 2014 ; Novikov et al, 2019 ), which may confer a greater risk for specific types of kidney stones. Moreover, a recent study of pooled analysis of data from clinical studies found that in 19% of patients, treatment with luseogliflozin resulted in increased serum uric acid, which may be due to reduced glomerular filtration of uric acid via the tubuloglomerular feedback ( Chino et al, 2022 ). Yet, another meta-analysis found no association of SGLT-2 inhibitors with nephrolithiasis ( Cosentino et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Uricosuria is a class effect; however, individual compounds were not found equal in this study. A Japanese analysis of three studies with luseogliflozin found both decreased and increased uric acid after 12 weeks, and this effect was dependent on the baseline uric acid concentration, glycosylated hemoglobin and glomerular filtration [ 89 ]. Thus, more research elucidating these differences is necessary.…”
Section: Other Metabolic and Blood Composition Consequencesmentioning
confidence: 99%